2015
DOI: 10.1016/j.ophtha.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Torque Teno Virus in Culture-Negative Endophthalmitis by Representational Deep DNA Sequencing

Abstract: Purpose To test the hypothesis that uncultured organisms may be present in cases of culture-negative endophthalmitis, by use of deep DNA sequencing of vitreous biopsies. Design Single center consecutive prospective observational study. Participants and Controls Aqueous or vitreous biopsies from 21 consecutive patients presenting with presumed infectious endophthalmitis, and seven vitreous samples from patients undergoing surgery for non-infectious retinal disorders. Methods Traditional bacterial and fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 43 publications
3
58
0
4
Order By: Relevance
“…Lastly, recent work showing high rates of torque teno virus in culture-negative endophthalmitis has blurred the previously sharp distinction between infectious and “sterile” endophthalmitis altogether. 18 …”
Section: Discussionmentioning
confidence: 99%
“…Lastly, recent work showing high rates of torque teno virus in culture-negative endophthalmitis has blurred the previously sharp distinction between infectious and “sterile” endophthalmitis altogether. 18 …”
Section: Discussionmentioning
confidence: 99%
“…A few studies have used BRiSK to detect organisms de novo [36, 37]. We performed a pilot study with 21 consecutive vitreous samples from post-procedural, presumed infectious endophthalmitis and 7 vitreous samples from routine vitrectomy cases without inflammation were compared with culture, 16S PCR, and BRiSK [36].…”
Section: Massive Parallel Sequencingmentioning
confidence: 99%
“…We performed a pilot study with 21 consecutive vitreous samples from post-procedural, presumed infectious endophthalmitis and 7 vitreous samples from routine vitrectomy cases without inflammation were compared with culture, 16S PCR, and BRiSK [36]. Fourteen of the 21 endophthalmitis samples were found to be bacterial culture-positive.…”
Section: Massive Parallel Sequencingmentioning
confidence: 99%
“…For example, one study revealed that fungi and viruses make‐up less than 2% of the microbial reads from conjunctival swabs . In another study, DNA analysis showed that 65% of healthy subjects were positive for torque teno virus, which has also been linked to culture‐negative cases of endophthalmitis . Other viruses have also been found at the ocular surface of asymptomatic subjects, suggesting that niches for viruses may exist at the ocular surface .…”
Section: The Ocular Microbiome‐myth or Fact?mentioning
confidence: 99%